Evaluation of the Relationship between Nutritional Status of COVID-19 Patients Admitted to the ICU and Patients’ Prognosis: A Cohort Study - Parsa Mohammadi; Hesam Aldin Varpaei; Alireza Khafaee pour khamseh; Mostafa Mohammadi; Mojgan Rahimi; Amirhossein Orandi (Journal of Nutrition and Metabolism)
Background. Malnutrition in COVID-19 critically ill patients can lead to poor prognosis. This study aimed to evaluate the association between nutritional status (or risk) and the prognosis of critically ill COVID-19 patients. In this study, prognosis is the primary outcome of “hospital mortality” patients. The second outcome is defined as “need for mechanical ventilation.” Methods and Materials. In this single-center prospective cohort study, 110 patients admitted to the Intensive Care Unit of Imam Khomeini Hospital Complex (Tehran, Iran) between April and September 2021 were enrolled. Participants formed a consecutive sample. MNA-SF, NRS-2002, mNUTRIC, and PNI scores were used to evaluate nutritional assessment. Patients’ lab results and pulse oximetric saturation SpO2/FiO2 (SF) ratio at the time of intensive care unit (ICU) admission were collected. Patients were screened for nutritional status and categorized into two groups, patients at nutritional risk and nonrisk. Results. Sixty-five (59.1%) of all patients were men. The overall range of age was 52 ± 15. Thirty-six (32.7%) of patients were obese (BMI ≥ 30). The hospital mortality rate was 59.1% (n = 65). According to the different criteria, malnutrition rate was 67.3% (n = 74) (NRS), 28.2% (n = 31) (MNA), 34.5% (n = 38) (mNUTRIC), and 58.2% (n = 64) (PNI). There was a statistically significant association between chronic kidney disease (CKD) and mNUTRIC risk (OR = 13.5, 95% CI (1.89–16.05), P=0.002), diabetes mellitus (DM) and MNA risk (OR = 2.82, 95% CI (1.01–7.83), P=0.041), hypertension (HTN) and MNA risk (OR = 5.63, 95% CI (2.26–14.05), P<0.001), and malignancy and mNUTRIC risk (P=0.048). The nutritional risk (all tools) significantly increased the odds of in-hospital death and need for mechanical ventilation. The length of stay was not significantly different in malnourished patients. Conclusion. In the critical care setting of COVID-19 patients, malnutrition is prevalent. Malnutrition (nutritional risk) is associated with an increased risk of need for mechanical ventilation and in-hospital mortality. Patients with a history of HTN, CKD, DM, and cancer are more likely to be at nutritional risk at the time of ICU admission.